PELATIHAN PEWARNAAN KAIN TENUN DENGAN MEMANFAATKAN TANAMAN PEKARANGAN RUMAH DI KELOMPOK TENUN SAKURA - Yolanda Naisumu; Polikarpia Wilhelmina Bani; Remigius Binsasi; Jefrianus Sanan (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Traditional community knowledge about plant species, especially home garden plants that produce natural dyes, can have a positive influence on the progress of science and technology in the textile sector. The existence of information about natural dyes of woven fabrics from plants in the yard of the house is expected to increase income because it can produce woven fabrics that have a higher selling value based on local wisdom. This service activity is carried out in 7 stages starting from the socialization stage to the stage of monitoring the coloring results. Community members were very enthusiastic in participating in the activities. The results of the extraction of dyes from plant organs in the yard of the house are directly applied to the threads that have been provided. Yarns resulting from natural dye from home garden plants can be directly marketed or previously woven and marketed to improve the welfare of each member Yarns resulting from natural dye from home garden plants can be directly marketed or previously woven and marketed to improve the welfare of each member.